2012
DOI: 10.1088/1674-1056/21/3/034501
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behaviors of dragonfly wing: relationship between configuration and deformation

Abstract: In this paper, the natural structures of a dragonfly wing, including the corrugation of the chordwise cross-section, the sandwich microstructure veins, and the junctions between the vein and the membrane, have been investigated with experimental observations, and the morphological parameters of these structural features are measured. The experimental result indicates that the corrugated angle among the longitudinal veins ranges from 80 • to 150 • , and the sandwiched microstructure vein mainly consists of chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…Micro-CT ( Jongerius and Lentink, 2010 ) was used to create three-dimensional (3D) high-resolution rendering of the cross-sectional corrugation on the chordwise profile of the forewing, and to aid understanding of the influence of cross-sectional corrugations on the spanwise bending of the forewing. Then, by combining the honeybee forewing venation and previous studies ( Combes and Daniel, 2003 ; Rajabi and Darvizeh, 2013 ; Ren et al, 2012 ; Chen et al, 2013 ; Kesel et al, 1998 ) on the wing venation, it was found that the leading edge vein was another factor influencing the span-chordwise anisotropy. In summary, even though the span-chordwise anisotropy of insect wings was previously reported, we submit that the published information is incomplete and there is a need, based on our present work, to integrate all the possible factors to explain and discuss this feature as comprehensively as possible.…”
Section: Introductionmentioning
confidence: 89%
“…Micro-CT ( Jongerius and Lentink, 2010 ) was used to create three-dimensional (3D) high-resolution rendering of the cross-sectional corrugation on the chordwise profile of the forewing, and to aid understanding of the influence of cross-sectional corrugations on the spanwise bending of the forewing. Then, by combining the honeybee forewing venation and previous studies ( Combes and Daniel, 2003 ; Rajabi and Darvizeh, 2013 ; Ren et al, 2012 ; Chen et al, 2013 ; Kesel et al, 1998 ) on the wing venation, it was found that the leading edge vein was another factor influencing the span-chordwise anisotropy. In summary, even though the span-chordwise anisotropy of insect wings was previously reported, we submit that the published information is incomplete and there is a need, based on our present work, to integrate all the possible factors to explain and discuss this feature as comprehensively as possible.…”
Section: Introductionmentioning
confidence: 89%
“…Taking into account that the spikes on the hill side of vein joints are usually larger than those on the valley side [ 17 ], they were modelled to have different dimensions (hill-sided spikes are about two times larger than those located on the valley side). The corrugation angle, in all models, was chosen to be about 150° [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are several studies available in the literature that employed finite-element (FE) method to numerically model dragonfly wings as a whole. However, given the structural complexities of insect wings, many of the previously developed models contain inevitable huge oversimplifications [ 23 , 24 ]. Therefore, in our opinion, comparative studies on individual wing components may serve as a much more useful approach to understand the role of each single component in the functionality of insect wings.…”
Section: Introductionmentioning
confidence: 99%
“…When the loads applied on the wing, the veins near the trailing edge area are more likely to be fractured under the long time of cyclic load. Before the appearance of cracks, the 3D truss‐like structure and surface morphology of the dragonfly wings reduce inertia moment and the stress at the wing tip, which is helpful for the flexible deformation of wings during flight (Combes and Daniel, ; Ren et al, ). The characteristics of structure and morphology can effectively reduce the generation of cracks, which play an important role in improving the antifatigue properties.…”
Section: Resultsmentioning
confidence: 99%
“…Dragonfly wings possess great stability and high load‐bearing capacity during flapping flight, glide, and hover, despite the fact that the wings are thin and light, accounting for 1–2% of the total body weight (Okamoto et al, ; Song et al, ; Zeng et al, ). The special hierarchical structure of the dragonfly wings remarkably improved the torsional deformation of dragonfly wing (Chen et al, 2008; Combes and Daniel, ; Ren et al, ), therefore, the flights of dragonfly wing with longitudinal veins are efficient and intelligent, and benefic for its biomechanical behavior (Chen et al, ; Park and Choi, ; Sun and Bhushan, ; Sun et al, ).…”
Section: Introductionmentioning
confidence: 99%